The role of systemic immune inflammation index in predicting melanoma - Tao, Qingxiu; Wang, Chunli; Zeng, Long; Mao, Mengjie; Lu, Yingchun; Wang, Chunyu; Liu, Bin (Frontiers in Oncology, 2025)
Many malignancies arise in the context of chronic infection, persistent irritation, or unresolved inflammation, and the inflammatory environment is closely associated with tumor cell proliferation and metastatic spread. The systemic immune-inflammation index (SII), calculated from peripheral lymphocyte, neutrophil, and platelet counts, has been investigated as a prognostic biomarker in several solid tumors, but its role in melanoma is not well defined. Data from the 2003–2018 cycles of the National Health and Nutrition Examination Survey (NHANES) were analyzed using multivariable logistic regression to assess the association between SII and melanoma. Subgroup analyses were conducted according to sex, age, marital status, body mass index, hypercholesterolemia, and smoking status. A cross-sectional study including 39,200 participants from eight NHANES cycles (2003–2018) was conducted, and logistic regression was applied to quantify the association between SII and melanoma. After categorizing SII into tertiles, the unadjusted model indicated that individuals in the highest tertile had a 57% higher melanoma risk compared with those in the lowest tertile (OR = 1.57; 95% CI, 1.06–2.34; p = 0.024). After adjusting for potential confounders, the highest SII tertile remained associated with a 48% increased risk (OR = 1.48; 95% CI, 1.01–2.01; p = 0.047). Higher SII levels were also significantly associated with increased risk in the hypercholesterolemia subgroup (OR = 1.33; 95% CI, 1.08–1.64; p = 0.008). These findings indicate a moderate positive association between SII and melanoma incidence, suggesting that SII may be a simple and accessible biomarker for early detection. To address the limitations of cross-sectional analysis, an external validation cohort was established at our tertiary oncology center. Between 2017 and 2018, 101 pathologically confirmed melanoma patients and 207 contemporaneous non-melanoma controls were recruited. In multivariable logistic regression, the highest SII tertile was associated with a 2.6-fold higher melanoma risk compared with the lowest tertile (OR = 2.60; 95% CI, 1.19–5.69; p = 0.017). These external data support SII as a potential indicator of melanoma risk; however, further validation in prospective cohort studies is required.